Respuesta :
Hello from MrBillDoesMath!
Answer:
2 (complex) solutions
x = 2 + i and x 2 - i
Discussion:
Rewrite x^2 = 4x - 5 as
x^2 -4x + 5 = 0
The solutions from the quadratic formula are
x = ( -(-4) +\- sqrt ( (-4)^2 - 4 (1)(5)) ) /2
x = ( 4 +\- sqrt(16-20)) )/2
x = ( 4 +\- sqrt(-4) ) /2
x = (4 +\- 2i) /2
x = 2 +\- i
Thank you,
MrB
Answer:
It does not have a solution.
Step-by-step explanation:
To solve this you just need to arrange the equation into the general formula:
x^2-4x+5=0
So we just insert that into the general formula:
[tex]x=\frac{-b+\sqrt{b^2-4ac} }{2a}[/tex]
Now you just have to insert the values into this formula:
[tex]x=\frac{-b+\sqrt{b^2-4ac} }{2a}\\x=\frac{-(-4)+\sqrt{16-4(5)} }{2*1}\\x=\frac{+4+\sqrt{-20} }{2}[/tex]
Since the square root is a negative number, you won´t be able to do that, so there is no solution for the equation.